Hak Waris Terhadap Individu yang Berpindah-Pindah Agama (Studi Kasus Putusan Nomor : 483/Pdt.G/2020/PN Dps) - I Putu Budi Astika; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
There are many cases of inheritance rights issues in Balinese indigenous peoples, which often cannot be resolved by means of deliberation (mediation) in traditional villages. These problems are mostly resolved through the Judiciary (Litigation). One of the problems that is being discussed is the inheritance rights of individuals who change religions in Balinese society. This research was conducted to examine the inheritance rights of individuals who change religions in Balinese society. The research method used in this research is normative legal research. This research uses a statutory approach. Sources of data used in this research are primary and secondary data. The data were analyzed using qualitative methods. The results of this research are: The regulation of inheritance rights has failed because in the Decree of the Main Assembly of Pekraman Village (MDP) Bali Number: 01/Kep/Psm-3/MDP Bali/X/2010 clearly states that descendants who move religion (ninggal kedaton) did not get the right to inherit. And inheritance for men who change religions is the same as (left kedaton) where the man does not get the right to inherit.